(untitled) - Mutea, Fridah Gacheri (Can Tho, 2020)
The deterioration signs of water quality in the Hau River are apparent. This study analyzed the water quality of the Hau River using standard procedures where 11 water quality parameters were analyzed using Principal component analysis (PCA) and Cluster Analysis (CA). The mapping of water quality was done for both dry and wet seasons, involving the 11 water quality parameters. The findings showed high levels of BOD, TSS, and Total Coliform, all year round. The PCA revealed that all the water quality parameters influenced the water quality of Hau River, thus the relevance for water sample scrutiny. The dendrogram of similarity between sampling sites showed a maximum similarity of 95.6%. The trend in AF showed that the concentrations of Total Suspended Solids (TSS), Biological Oxygen Demand (BOD), and Phosphate (PO43-) in the downstream were 1.29, 1.53, and 1.52, times, respectively, greater than the upstream levels. It can, therefore, be concluded that most of the water quality parameters in Hau River were within the desirable ranges for aquaculture except DO, which was slightly below while, on the other hand, BOD and Total Coliform were above the desirable ranges for aquaculture. Geographcal Information System results showed that temperature was maximum in the upstream and minimum in the downstream in both dry and rainy season. As for BOD, the concentration increased from upstream towards the downstream during both seasons. It was notable that for Dissolved Oxygen, site CT9 had the least levels in both seasons. Besides, Total Coliform had higher concentrations at the canals as compared to the main channel of the river, which was contrary to pH results on the map where the canals recorded minimum levels as compared to the main channel. Despite most of the parameters analyzed supporting aquaculture production, caution is needed in the regulation of point sources pollution to undertake sustainable aquaculture production.
Keywords: Nuôi cá,Fish culture; Nghiên cứu,Research